Indonesia's Defense Diplomacy through the MONUSCO Mission in the Democratic Republic of the Congo - Mirajiah, Risalatu; Ningsih, Wilda (Jurnal Sains Sosio Humaniora, 2026)
This study analyzes Indonesia’s defense diplomacy through its participation in the United Nations Organization Stabilization Mission in the Democratic Republic of the Congo (MONUSCO). The prolonged conflict in the Democratic Republic of the Congo has created multidimensional security challenges that require collective international responses through United Nations peacekeeping operations. Indonesia’s involvement in MONUSCO reflects not only its commitment to maintaining international peace and security, but also its strategic efforts in strengthening its role within multilateral security cooperation. This research employs a qualitative descriptive method through literature studies, document analysis, and the examination of official reports from the United Nations, MONUSCO, and the Indonesian National Armed Forces. The study uses the theory of defense diplomacy to examine how Indonesia utilizes peacekeeping operations as an instrument to support foreign policy objectives and strengthen international cooperation. The findings show that Indonesia carries out defense diplomacy through peacekeeping activities, civil-military cooperation, humanitarian assistance, and Quick Impact Projects (QIP) aimed at supporting local communities in conflict areas. These activities contribute to strengthening Indonesia’s international image, enhancing military professionalism, and building trust with local communities. However, Indonesia also faces operational and security challenges in implementing defense diplomacy within the complex dynamics of multidimensional peacekeeping missions. This study concludes that Indonesia’s participation in MONUSCO represents a form of cooperative defense diplomacy that combines security and humanitarian approaches in supporting international peace efforts.